Teaching during Pandemic Years: Faculty Experiences from Government-Funded Universities in the Philippines - Potoy, Mark Herman S.; Cantina, Jovelyn M.; Banquiao, Quindhe M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Due to this significant and disruptive change in teaching and learning, teachers, who serve as frontline educators, are faced with several difficulties. This study employed a qualitative phenomenology methodology to investigate faculty members' experiences while lecturing at public universities and colleges in the Philippines during the pandemic and the pedagogical solutions they employed to overcome these difficulties. According to the study, five themes surfaced from instructors' real-life experiences: (1) students’ negative attitudes toward learning; (2) health-related issues; (3) inaccessibility and poor internet connection; (4) limited flexible learning pedagogies; and (5) unavailability and/or insufficiency of ICT resources. Negative student attitudes, health-related problems, poor internet accessibility, a lack of flexible learning pedagogies, and an absence or limited availability of ICT resources are all significant predictors of how well students will engage in and how well teachers will perform when delivering high-quality instruction during a pandemic. It has been determined that the difficulties faced by the faculty play a significant role in predicting how well student engagement and teachers' ability to deliver high-quality instruction during pandemics will fare. Therefore, the government must allot enough money to modernize the facilities and internet connectivity to deliver online instruction, as well as to provide instructors with training and professional growth in online tools and pedagogy. It is possible to implement and sponsor a training program that will provide the faculty with the tools they need to meet the challenges of the new normal.